Methane and nitrous oxide emissions in rice-crab culture systems of northeast China - Ang Wang; Xuzhou Ma; Jing Xu; Weiqun Lu (Aquaculture and Fisheries, 2019)
Rice-crab integrated ecosystem has been confirmed to improve the ecological environment and brought greater economic benefits. In order to know greenhouse gases methane (CH4) and nitrous oxide (N2O) emissions in rice-crab system, they were quantified from a flooding rice field in northeast China, as affected by integrated rice-crab cultivation. Three treatments with three replications each were given: (1) RC1- rice with crab (megalopa), (2) RC2 - rice with crab (juvenile), (3) RM - rice only. Seasonal CH4 and N2O fluxes were measured by closed chamber method. Compared with RM treatment, RC1 and RC2 treatments greatly enhanced the cumulative seasonal CH4 emissions (by 36.8% and 29.2%, respectively), and reduced the cumulative seasonal N2O emissions (by 28.2% and 19.7%, respectively). Across treatments, CH4 represented over 97% of total global warming potential (GWP) and as a result, RC1 and RC2 treatments significantly increased the GWP than RM treatment. Although the GWP was highest in RC1 treatment, it provided highest rice yield (8780 kg/ha) and net ecosystem economic budget (NEEB, 23,159 Yuan/ha) over RM (7668 kg/ha, 15,130 Yuan/ha) and RC2 (8042 kg/ha, 18,713 Yuan/ha) treatments. To summarize, cultivation of megalopa in rice field is a better strategy to optimize the economic and environmental benefits in northeast China. Keywords: Rice-crab integrated ecosystem, Methane, Nitrous oxide, Rice yield, Global warming potentials, Net ecosystem economic budget